Assessing the impact of within crop heterogeneity ('patchiness') in young Miscanthus × giganteus fields on economic feasibility and soil carbon sequestration. Issue 5 (17th May 2013) - Zimmermann, Jesko; Styles, David; Hastings, Astley; Dauber, Jens; Jones, Michael B
Abstract In Ireland, Miscanthus × giganteus has the potential to become a major feedstock for bioenergy production. However, under current climatic conditions, Ireland is situated on the margin of the geographical range where Miscanthus production is economically feasible. It is therefore important to optimize the yield and other ecosystem services such as carbon sequestration delivered by the crop. A survey of commercial Miscanthus fields showed a large number of areas with no Miscanthus crop cover. These patches can potentially lead to reduced crop yields and soil carbon sequestration and have a significant negative impact on the economic viability of the crop. The aim of this research is to assess patchiness on a field scale and to analyse the impacts on crop yield and soil carbon sequestration. Analysis of aerial photography images was carried out on six commercial Miscanthus plantations in south east Ireland. The analysis showed an average of 372.5 patches per hectare, covering an average of 13.7% of the field area. Using net present value models and a financial balance approach it was shown that patchiness has a significant impact on payback time for initial investments and might reduce gross margins by more than 50%. Total and Miscanthus‐derived soil organic carbon was measured in open patches and adjacent plots of high crop density showing significantly lower Miscanthus‐derived carbon stocks in open patches compared to high crop‐density patches (0.47Mg C ha−1 ± 0.42 SD and 0.91Mg C ha−1 ± 0.55 SD). Using geographic information system (GIS) it was shown that on a field scale Miscanthus‐derived carbon stocks were reduced by 7.38% ± 7.25 SD. However, total soil organic carbon stocks were not significantly different between open patches and high crop density plots indicating no impact on the overall carbon sequestration on a field scale over 3–4 years since establishment for these Miscanthus sites.